Polityka przestrzenna a współczesna polityka regionalna - zarys problemu - Markowska-Przybyła, Urszula (Spatial development policy versus contemporary regional policy - outline of a problem, 2006)
Contemporary conditions of socio-economic development create special challenges in regional policy. Both the necessity for increasing efficiency of national economies and the need of equalizing disparities, which arise naturally, have created a new approach to regional policy, which is rising competitiveness of regions. The necessity for reconciling “efficiency” with “equality” appeared also in different Helds of economic policy, among other things in policy of spatial development. For the sake of existing relationships implications of these policies were presented. In particular, the conception of national spatial policy and spatial policy of EU were shown.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 226-237